Pengaruh Lingkungan Keluarga Terhadap Pilihan Karier Berwirausaha Pada Remaja - Dina Aulia; Gita Kusuma Dewi Harahap; Nurul Amaliyah Simanungkalit; Reginawati Sitompul; Rosi Dearan S Lingga; Syarifah Khalisa Adilla (CV. Ulil Albab Corp, 2024)
Career choice is an important aspect of individual development, especially during adolescence. Among the various career options available, entrepreneurship is becoming an increasingly attractive alternative. The choice to become an entrepreneur is not only driven by external factors but also driven by the internal environment, especially the family. This study aims to analyze the influence of the family environment on entrepreneurial career choices in adolescents. This study uses quantitative methods. Data were collected through questionnaires filled out by 75 adolescents aged 12 to 22 years. The analysis technique used was simple linear regression to test the relationship between family support and entrepreneurial career choice in adolescents. The results showed that the family environment has a significant effect on entrepreneurial career choice, with a coefficient of determination (R²) of 0.607 This means that 60.7% of entrepreneurial interest is influenced by the family environment, while the rest is influenced by other factors. These findings are expected to be useful to add insight into the family to create an environment that supports entrepreneurial careers among adolescents.